Heat and Thermodynamics - Sprackling, Michael (College Work Out Series, 1993)
Heat and Thermodynamics presents the core topics in thermal physics in a concise format using the characteristic, problem based learning approach; the trade mark of the College Work Out Series. Written for undergraduates taking their first course in thermal physics, the book has combined the aim of promoting understanding through problem solving and, by putting many of the problems in traditional examination form, providing exam preparation. The author begins with a summary of the more important basic concepts and establishes basic terminology and outlook before examining each of the core areas subsequent chapters